Puasa Senin-Kamis dengan Fungsi Kognisi Lanjut Usia - Rumaisha Ummu Syuhada; M. Nurhalim Shahib; Sara Puspita (Bandung Conference Series: Medical Science, 2023)
Abstract. Cognition is defined as a thought process in the brain, using sensory input to the brain plus information that has been stored as memory. Cognitive function is influenced by one of them by fasting. This study aims to analyze the relationship between the intensity of Monday-Thursday fasting and cognitive function in the elderly at the Bandung City Nursing Home. This type of research is a quantitative research with analytical methods accompanied by a cross sectional approach. Sampling using probability sampling technique with total sampling method obtained 30 respondents. The method of data collection was carried out using the MMSE questionnaire instrument and interviews about fasting which were analyzed by the chi square test with the results of bivariate analysis showing a relationship between the intensity of fasting on Mondays and Thursdays with cognitive function in the elderly at the Nursing Home in Bandung City (p=0.002). The conclusion in this study is that there is an influence between intermittent fasting and cognitive function in the elderly at the Nursing Home, Bandung City. Abstrak. Kognisi diartikan sebagai proses berpikir pada otak, dengan menggunakan input sensorik yang menuju otak ditambah informasi yang telah disimpan sebagai memori. Fungsi kognisi dipengaruhi salah satunya oleh puasa. Penelitian ini bertujuan untuk menganalisis hubungan antara intensitas puasa Senin Kamis dengan fungsi kognisi pada lanjut usia di Panti Werdha Kota Bandung. Jenis penelitian ini adalah penelitian kuantitatif dengan metode analitik yang disertai dengan pendekatan cross sectional. Pengambilan sampel menggunakan tehnik probability sampling dengan metode total samplingdidapatkan 30 responden. Cara pengumpulan data dilakukan menggunakan instrumen kuesioner MMSE dan wawancara mengensi puasa yang di analisis dengan uji chi square dengan hasil analisis bivariat menunjukkan adanya hubungan antara intensitas puasa Senin Kamis dengan fungsi kognisi pada lanjut usia di Panti Werdha Kota Bandung (p=0,002). Kesimpulan dalam penelitian ini adalah terdapat hubungan antara puasa Senin Kamis dengan fungsi kognisi pada lanjut usia di Panti Werdha Kota Bandung.